Enhancing fungal diversity in ex-coal mine soils through tillage and organic waste - ZAINUDIN ZAINUDIN; DYAH ROESWITAWATI; ADI SUTANTO; ALI IKHWAN; RORO KESUMANINGWATI (Society for Indonesian Biodiversity, 2025)
Abstract. Zainudin, Roeswitawati D, Sutanto A, Ikhwan A, Kesumaningwati R. 2025. Enhancing fungal diversity in ex-coal mine soils through tillage and organic waste. Biodiversitas 26: 3516-3527. This study investigates the effects of tillage depth, urban organic waste application, and incubation period on fungal diversity in soils from former coal mining sites in Samarinda, East Kalimantan, Indonesia. Using a Box-Behnken design within Response Surface Methodology (RSM), three factors, tillage depth (5-15 cm), incubation period (60-120 days), and organic waste application (20-60 tons ha?¹) were tested across 17 treatment combinations. Fungal populations were quantified using Potato Dextrose Agar (PDA) through serial dilution and colony counting. Fungal richness increased significantly with incubation time: four species were found at 60 days (Rhizoctonia sp., Aspergillus fumigatus Fresen., Chrysonilia sp., Aspergillus niger Tiegh.); six at 90 days (Aspergillus flavus Link, A. fumigatus, A. niger, Gliocladium sp., Trichoderma sp., Penicillium sp.); and seven at 120 days (A. flavus, A. fumigatus, Rhizoctonia sp., A. niger, Gliocladium sp., Trichoderma sp., Colletotrichum sp.). Diversity indices also improved with time. At 60, 90, and 120 days, Shannon-Wiener index (H) values were 1.369, 1.691, and 1.846 (medium), dominance (D) values were 0.259, 0.197, and 0.174 (low), and Margalef indices (Dmg) were 1.365, 1.698 (low), and 2.502 (medium). Evenness values ranged from 0.944 to 0.987, indicating an almost even fungal distribution. Statistical analysis revealed that only the incubation period significantly affected fungal population density (p < 0.05), while tillage depth (p = 0.3654) and organic waste application (p = 0.6662) did not. The resulting regression model was: Total fungal colony = 10.24 + 2.12A + 5.63B + 1.0000C. This study contributes novel insights into the integrated effects of soil management practices on fungal diversity in tropical post-mining soils an area previously underexplored. The application of RSM allowed optimization of interacting variables. The findings reinforce the ecological role of fungi as bioindicators and agents for soil restoration, emphasizing incubation duration as a key driver in enhancing microbial recovery for sustainable land reclamation.